Quality newborn care in East New Britain, Papua New Guinea: measuring early newborn care practices and identifying opportunities for improvement - Alyce N. Wilson; Pele Melepia; Rose Suruka; Priscah Hezeri; Dukduk Kabiu; Delly Babona; Pinip Wapi; Naomi Spotswood; Meghan A. Bohren; Joshua P. Vogel; Angela Kelly-Hanku; Alison Morgan; et al. (BMC, 2022)
Abstract Background Renewed attention and investment is needed to improve the quality of care during the early newborn period to address preventable newborn deaths and stillbirths in Papua New Guinea (PNG). We aimed to assess early newborn care practices and identify opportunities for improvement in one province (East New Britain) in PNG. Methods A mixed-methods study was undertaken in five rural health facilities in the province using a combination of facility audits, labour observations and qualitative interviews with women and maternity providers. Data collection took place between September 2019 and February 2020. Quantitative data were analysed descriptively, whilst qualitative data were analysed using content analysis. Data were triangulated by data source. Results Five facility audits, 30 labour observations (in four of the facilities), and interviews with 13 women and eight health providers were conducted to examine early newborn care practices. We found a perinatal mortality rate of 32.2 perinatal deaths per 1000 total births and several barriers to quality newborn care, including an insufficient workforce, critical infrastructure and utility constraints, and limited availability of essential newborn medicines and equipment. Most newborns received at least one essential newborn care practice in the first hour of life, such as immediate and thorough drying (97%). Conclusions We observed high rates of essential newborn care practices including immediate skin-to-skin and delayed cord clamping. We also identified multiple barriers to improving the quality of newborn care in East New Britain, PNG. These findings can inform the development of effective interventions to improve the quality of newborn care. Further, this study demonstrates that multi-faceted programs that include increased investment in the health workforce, education and training, and availability of essential equipment, medicines, and supplies are required to improve newborn outcomes.